Analisis Perbedaan Nilai Paparan Medan Listrik pada Biji Buncis (Phaseolus vulgaris l.) Terhadap Panjang Tanaman yang Dihasilkan - Asviyatu Nisa'; Muhammad Helmi Hakim; Yuanita Amalia Hariyanto (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
The effect of an electric field on plant roots can affect plant growth and development, plants growing in an electric field cause cell and tissue polarization and can affect plant root growth. This study aims to determine the effect of the electric field on the length of the bean plant. In this study, the electric field application used for field treatment was 0.5 kV/m, 1 kV/m, 1.5 kV/m, and 2 kV/m for 60 minutes. The results obtained from this study indicate that the electric field can accelerate the growth of bean plant length. The most suitable electric field to accelerate germination growth is an electric field of 1 kV/m.